2018
DOI: 10.1039/c8lc00450a
|View full text |Cite
|
Sign up to set email alerts
|

Droplet microarray: miniaturized platform for rapid formation and high-throughput screening of embryoid bodies

Abstract: Stem cells are influenced by various factors present in their in vivo microenvironment, such as interactions with neighboring cells, the extracellular matrix or soluble molecules. This demonstrates the high complexity of the in vivo microenvironment. Hence, many advances have been made in developing 3D screening models mimicking this complexity and the in vivo-like state in order to ensure more biomedically relevant investigations in drug discovery. In the field of stem cell research embryoid bodies are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Recently, we developed the Droplet Microarray (DMA), a miniaturized platform for cell‐based high‐throughput screenings . The Droplet Microarray consists of an array of hydrophilic spots on superhydrophobic background and exhibits extreme contrast in wettability between these areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed the Droplet Microarray (DMA), a miniaturized platform for cell‐based high‐throughput screenings . The Droplet Microarray consists of an array of hydrophilic spots on superhydrophobic background and exhibits extreme contrast in wettability between these areas.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] Recently, we developed the Droplet Microarray (DMA), a miniaturized platform for cell-based high-throughput screenings. [35][36][37][38][39][40] The Droplet Microarray consists of an array of hydrophilic spots on superhydrophobic background and exhibits extreme contrast in wettability between these areas. Due to this extreme contrast a high-density array of homogeneous, separated and stable nanodroplets can be formed on the surface of the Droplet Microarray.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is based on a programmable noncontact piezoelectric inkjet bioprinter with a resolution of 5 ”m and a minimum deposition volume of 300 pL. Such a system has been frequently applied in researches, especially for ultra-low volume liquid handling of nanoparticles (Scherbahn et al, 2016), drugs (Tronser et al, 2018), and biomolecules, such as proteins (Kilb et al, 2019) and antibodies (Marquette et al, 2012;Schulz et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…We showed that by using the DMA platform and only 100 cells and 300 times fewer compounds and reagents, we obtained the same results as if we had employed conventional 384-well plates and 20,000 cells per each well. We have demonstrated our system in 2D, however, as we have previously shown that the DMA platform is compatible with culturing cells in 3D environments by means of scaffolds 34,35 or by promoting the self-organization of cells. 35 The possibility of culturing cells in 3D gives rise to even more physiologically relevant applications using primary patient-derived cells.…”
Section: Discussionmentioning
confidence: 96%
“…We have demonstrated the use of the DMA platform for the screening of cells of adherent 30,33 and suspension 29 nature in 2D, as well as in 3D environments. 34,35 In this paper, we have extended application of our miniaturized platform for the miniaturized DSRT on suspension primary patient-derived CLL cells. By using the DMA platform, we were able to reduce the consumption of cells by a factor of 200 compared with 384-well plates.…”
Section: Introductionmentioning
confidence: 99%